Hubungan Kecerdasan Emosional dengan Academic Bouyancy pada Siswa SMA Kabupaten Pasaman - Herlyza Putri; Zulian Fikry (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This research aims to see a picture of the correlation between emotional inntelligance and academic buoyancy in high school students in Pasaman Regency. This type of research uses quantitative correlational research methods. The research subject were 341 people obtained through propotional stratified random sampling teschniques. The data collection tool uses an emotional resilience scale consisting of 32 items with a reliability value of 0.872 and an emotional intelligence scale consisting of 30 items with a reliability valie oof 0.807. The data processed using the Spearmen Rho correlation statistical technique. Based on research result with an r value of 0.930 with p=0.001 (p<0.01), it shiws that there is a very significant positive relathionship between emotional intelligence and academic striving for students in Pasaman Regency. This shows that the higher the emotional intelligence, the higher the fighting power of students in Pasaman Regency.